Thin SnOx films for surface plasmon resonance enhanced ellipsometric gas sensing (SPREE) - Fischer, Daniel; Hertwig, Andreas; Beck, Uwe; Lohse, Volkmar; Negendank, Detlef; Kormunda, Martin; Esser, Norbert (Beilstein Journal of Nanotechnology, 2017)
Background: Gas sensors are very important in several fields like gas monitoring, safety and environmental applications. In this approach, a new gas sensing concept is investigated which combines the powerful adsorption probability of metal oxide conductive sensors (MOS) with an optical ellipsometric readout. This concept shows promising results to solve the problems of cross sensitivity of the MOS concept.Results: Undoped tin oxide (SnOx) and iron doped tin oxide (Fe:SnOx) thin add-on films were prepared by magnetron sputtering on the top of the actual surface plasmon resonance (SPR) sensing gold layer. The films were tested for their sensitivity to several gas species in the surface plasmon resonance enhanced (SPREE) gas measurement. It was found that the undoped tin oxide (SnOx) shows higher sensitivities to propane (C3H8) then to carbon monoxide (CO). By using Fe:SnOx, this relation is inverted. This behavior was explained by a change of the amount of binding sites for CO in the layer due to this iron doping. For hydrogen (H2) no such relation was found but the sensing ability was identical for both layer materials. This observation was related to a different sensing mechanism for H2 which is driven by the diffusion into the layer instead of adsorption on the surface.Conclusion: The gas sensing selectivity can be enhanced by tuning the properties of the thin film overcoating. A relation of the binding sites in the doped and undoped SnOx films and the gas sensing abilities for CO and C3H8 was found. This could open the path for optimized gas sensing devices with different coated SPREE sensors.
Keywords: doped tin oxide; ellipsometry; gas sensing; surface plasmon resonance; thin films; transparent conductive oxides

(untitled) - Arshak, K.; Moore, E.; Lyons, G. M.; Harris, J.; Clifford, S. (Sens. Rev., 2004)

(untitled) - Bakker, E.; Telting-Diaz, M. (Anal. Chem., 2002)

(untitled) - Hodgkinson, J.; Tatam, R. P. (Meas. Sci. Technol., 2013)

(untitled) - Liu, Y.; Parisi, J.; Sun, X.; Lei, Y. (J. Mater. Chem. A, 2014)

(untitled) - Barsan, N.; Koziej, D.; Weimar, U. (Sens. Actuators, B, 2007)

(untitled) - McAleer, J. F.; Moseley, P. T.; Norris, J. O. W.; Williams, D. E.; Taylor, P.; Tofield, B. C. (Mater. Chem. Phys., 1987)

(untitled) - Becker, T.; Ahlers, S.; Bosch-von Braunmühl, C.; Müller, G.; Kiesewetter, O. (Sens. Actuators, B, 2001)

(untitled) - Preiß, E. M.; Rogge, T.; Krauß, A.; Seidel, H. (Sens. Actuators, B, 2016)

(untitled) - Sun, Y.-F.; Liu, S.-B.; Meng, F.-L.; Liu, J.-Y.; Jin, Z.; Kong, L.-T.; Liu, J.-H. (Sensors, 2012)

(untitled) - Das, S.; Jayaraman, V. (Prog. Mater. Sci., 2014)

(untitled) - Ray, S. C.; Karanjai, M. K.; Dasgupta, D. (Thin Solid Films, 1997)

(untitled) - Jin, Z.; Zhou, H.-J.; Jin, Z.-L.; Savinell, R. F.; Liu, C.-C. (Sens. Actuators, B, 1998)

(untitled) - Briand, D.; Labeau, M.; Currie, J. F.; Delabouglise, G. (Sens. Actuators, B, 1998)

(untitled) - Shishkin, N. Y.; Zharsky, I. M.; Lugin, V. G.; Zarapin, V. G. (Sens. Actuators, B, 1998)

(untitled) - Kormunda, M.; Pavlik, J. (Vacuum, 2011)

(untitled) - Kormunda, M.; Fischer, D.; Hertwig, A.; Beck, U.; Sebik, M.; Pavlik, J.; Esser, N. (Thin Solid Films, 2015)

(untitled) - Das, D.; Banerjee, R. (Thin Solid Films, 1987)

(untitled) - Fischer, D.; Hertwig, A.; Beck, U.; Negendank, D.; Lohse, V.; Kormunda, M.; Esser, N. (Appl. Surf. Sci., 2016)

(untitled) - Kormunda, M.; Fischer, D.; Hertwig, A.; Beck, U.; Sebik, M.; Esser, N. (Phys. Status Solidi A, 2016)

(untitled) - Nooke, A.; Beck, U.; Hertwig, A.; Krause, A.; Krüger, H.; Lohse, V.; Negendank, D.; Steinbach, J. (Sens. Actuators, B, 2010)

(untitled) - Nooke, A.; Beck, U.; Hertwig, A.; Krause, A.; Krüger, H.; Lohse, V.; Negendank, D.; Steinbach, J. (Thin Solid Films, 2011)

(untitled) - Beck, U.; Hertwig, A.; Kormunda, M.; Krause, A.; Krüger, H.; Lohse, V.; Nooke, A.; Pavlik, J.; Steinbach, J. (Sens. Actuators, B, 2011)

(untitled) - Arwin, H.; Poksinski, M.; Johansen, K. (Appl. Opt., 2004)

Ellipsometry of Functional Organic Surfaces and Films - Arwin, H. (TIRE and SPR-Enhanced SE for Adsorption Processes, 2014)

(untitled) - Oates, T. W. H.; Wormeester, H.; Arwin, H. (Prog. Surf. Sci., 2011)

(untitled) - Azzam, R. M. A.; Bashara, N. M.; Thorburn Burns, D. (Anal. Chim. Acta, 1987)

Spectroscopic ellipsometry: principles and applications - Fujiwara, H. (John Wiley & Sons, 2007)

Surface plasmons on smooth and rough surfaces and on gratings - Raether, H. (Springer, 1988)

(untitled) - Owens, J. C. (Appl. Opt., 1967)

(untitled) - Homola, J.; Yee, S. S.; Gauglitz, G. (Sens. Actuators, B, 1999)

(untitled) - Li, M.; Cushing, S. K.; Wu, N. (Analyst, 2015)

(untitled) - Sakai, G.; Baik, N. S.; Miura, N.; Yamazoe, N. (Sens. Actuators, B, 2001)

(untitled) - Sung, S. S.; Hoffmann, R. (J. Am. Chem. Soc., 1985)